The impact of computer game-making on the creativity of elementary students - M. Roshanian Ramin (Fanāvarī-i āmūzish, 2020)
Background and Objectives: Today Computer games are one of the most effective media among various educational media. However, playing games can be used as a training method in education process. But in the opinion of many researchers, the making the game by the students can have deeper effects and it is an instructive and enjoyable experience for people, especially students. Computer game-making will stimulate thinking and creativity because in this action individual engaged in the multi-dimension activities. Due to the computer game-making by students is the new phenomenon and lack of enough research on the impact of this activity on creativity, there is a need for more research in this area. In this regard, the main purpose of this study was to investigate the effect of computer game-making on the creativity of elementary male students and sub-objectives were include: 1-Investigating the effect of computer game-making on the fluid dimension of creativity. 2- Investigating the effect of computer game making on the originality dimension of creativity. 3-Investigating the effect of computer game making on the flexibility dimension of creativity. 4- Investigating the effect of computer game making on the expansion dimension of creativity. Materials and Methods: The research method in this study was a quasi-experimental pre-test and post-test design with a control group. The statistical population was all boys' primary schools in the city of Islamshahr. One of these schools was selected. The sample of this study was 40 students from fourth to sixth grade who were selected using simple random sampling method and were randomly assigned to the control and experimental groups. The data collection tool was the Torrance Form B Creativity Test, which includes four subscales: fluidity, flexibility, originality, and expansion. The method of data collection was survey and the method of data analysis was differential t-test. Findings: Data analysis showed that computer game-making had a positive effect on creativity and its dimensions. Regarding the sub-hypotheses, the results showed that the mean score of the fluidity dimension of creativity in the experimental group was 9.21 with a standard deviation of 4.52 and the mean score of the control group was 2.25 with a standard deviation of 1.43. Analysis of the data showed that the experimental group experienced more changes in the creative fluid dimension than the control group and their fluidity increased  compare to before playing, (sig 0.001). Therefore, the research hypothesis was confirmed at the level of P Conclusion: game-making involves the user in a real multidimensional problem, and it can provide the context for fostering creativity. Game-making required the presentation of new ideas in the process of designing and producing games, and students saw the result of their work objectively, they had an inner motivation to keep working and continued to complete their ideas as well as come up with new ideas, and this is the point that has been emphasized in theories of creativity.   ===================================================================================== COPYRIGHTS  ©2020 The author(s). This is an open access article distributed under the terms of the Creative Commons Attribution (CC BY 4.0), which permits unrestricted use, distribution, and reproduction in any medium, as long as the original authors and source are cited. No permission is required from the authors or the publishers.  =====================================================================================